POSTOPERATIVE URINARY COMPLICATIONS IN MAJOR ABDOMINAL SURGERY: INCIDENCE, RISK FACTORS, AND UROLOGIC INTERVENTIONS: CLINICAL PRACTICE AND A SYSTEMATIC REVIEW - Dr. Cemoon Effendi; Dr. Amna Aziz; Dr. Abdul Rauf; Dr. Abdul Rauf; Dr. Nawaid Farooque Khan; Dr. Amber Shams (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Postoperative urinary complications (PUCs) remain an under-recognized yet clinically significant cause of morbidity following major abdominal surgery. This review synthesizes current evidence regarding the incidence, risk factors, pathophysiology, and management of postoperative urinary retention (POUR), catheter-associated urinary tract infections (CAUTIs), and detrusor dysfunction. A systematic search of PubMed, Scopus, and Web of Science (2000–2024) identified 31 high-quality studies involving over 45,000 surgical patients. The pooled incidence of PUCs ranged from 7% to 25%, with POUR being the most prevalent. Risk factors included advanced age, male sex, diabetes mellitus, prolonged operative time, neuraxial anesthesia, high perioperative fluid administration, opioid analgesia, and delayed mobilization. Evidence supports preventive strategies such as routine bladder scanning, time-bound catheter removal, opioid-sparing multimodal analgesia, and early ambulation. Implementation of standardized urinary care pathways reduced complication rates by up to 50% and decreased hospital stay by 1–2 days. Despite progress, heterogeneity in definitions and outcome measures limits data comparability. Multidisciplinary collaboration and standardized guidelines are essential to reduce PUC incidence, optimize resource use, and improve surgical recovery outcomes.